Atypical Presentation of Amyloidosis in a Female Patient with Muscle Weakness - Raziyeh Lashkari; Maryam Loghman; Leila Aghaghazvini; Hiva Saffar; Bentolhoda Ziaadini; Reza Shahriarirad; Mohammad Nekooeian; Mohammad Nejadhosseinian; Majid Alikhani (Case Reports in Medicine)
Muscle involvement represents a well-recognized but rare manifestation of amyloidosis. Here, we report a 40-year-old female who presented with muscle weakness, musculoskeletal pain, and proteinuria, which was eventually diagnosed as myopathic amyloidosis based on muscle biopsy results. A multidisciplinary approach appears to be the cornerstone of the diagnostic work up for recognizing the unusual amyloid myopathy.